TINGKAT KETERAMPILAN PETANI TERHADAP PENGOLAHAN PASCA PANEN LADA DI KECAMATAN PONRE KABUPATEN BONE - Arwati, Sitti (Jurnal Ilmiah Ecosystem, 2018)
SITTI ARWATI. Level of Skill of Farmers Towards Postharvest Processing of Pepper (Piper nigrum L.) in Ponre District, Bone Regency.The research objective is to determine the level of farmers' skills in pepper postharvest processing. The population is 251 farmers, the sample used is 15% of the total population of pepper farmers, which is 40 people.The results showed that the level of skill of farmers in the postharvest processing of pepper was in the high category reaching 58% or farmers were skilled in conducting postharvest processing and postharvest handling, because farmers carried out postharvest handling and produced pepper with quality standards that were competitive with prices which is high so that it can meet the needs of life and improve the welfare of pepper farmers.